STOCK PRICE DETERMINANTS IN THE INDONESIAN CAPITAL MARKET: INFLATION, EXCHANGE RATES, DIVIDEND POLICY, AND THE MODERATING ROLE OF COMPANY SIZE - Ananda Egi Aulia Aziza; Sahroni; Zulfitra (ZILLZELL MEDIA PRIMA, 2026)
This study examines the influence of inflation, exchange rates, and dividend policy on stock prices with firm size as a moderating variable in LQ 45 companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employs a quantitative approach with an associative method using panel data regression analysis. The population consists of LQ 45 companies listed on the IDX, with a sample of 21 companies selected through purposive sampling, yielding 105 firm-year observations. Secondary data were obtained from the Indonesia Stock Exchange, Badan Pusat Statistik, and Bank Indonesia. The analysis was conducted using EViews 10 with the Fixed Effect Model (FEM). The results indicate that inflation has a significant negative effect on stock prices, exchange rates have a significant negative effect on stock prices, and dividend policy has no significant effect on stock prices. Simultaneously, inflation, exchange rates, and dividend policy collectively exert a significant influence on stock prices. Furthermore, firm size moderates the relationship between exchange rates and stock prices but does not moderate the relationships between inflation and stock prices nor between dividend policy and stock prices. These findings suggest that investors should closely monitor macroeconomic factors when making investment decisions, and corporate management should strengthen foreign exchange risk management strategies.